METAFISIKA POLITIK: MENIMBANG KEKUATAN ARISTOKRASI DALAM PILKADA BELU DAN MALAKA TAHUN 2020 - Bouk, Hendrik Saku (JAP UNWIRA, 2020)
AbstractThis writing intends to describe the carrying out of election of district heads of Belu and Malaka regencies of the East Nusa Tenggara Province in December 2020. This paper is of the opinion that the election of district heads in these two regencies involved the perspective of political metaphysics. According to indigenous tradition of the Belunese and the Malakans, the metaphysical power is transformed into the personality of the raja. Raja is the representation of the divine, the incarnation of god (Maromak Oan) and endowed politically with rights to govern. In the general election of the Malaka and  Belu district heads, the pair candidates running for the posts of regent and vice regent did their best to win  the electoral contestation by building their political power through the coalition of political parties, through campaign for mass support, through political physics that mobilizes all political machinery as well as through pataphysics that make use of the virtual networks.  Nevertheless, the coalition of political parties still take into account the power of metaphysical politics  based on aristocracy. The nobilities are considered worthy to become the persons endowed with privileges to govern. Therefore the election of district heads does not necessarily always have to do with coalition, campaign and money politics, but also with tradition and belief of the voters who demonstrate their preference to the candidates from the aristocratic circles.